The effect of velocity-based resistance training (VBT) on lower-limb strength performance in male collegiate boxers: a randomized controlled trial - Han, Yemin; Xie, Yiqing; Zhang, Zhen; García-Ramos, Amador (Frontiers in Physiology, 2025)
BackgroundBoxing performance heavily relies on lower-limb strength and power. Velocity-based resistance training (VBT), which adjusts load and repetition volume using real-time velocity feedback, may provide a more individualized and effective approach compared to traditional percentage-based training (PBT). However, its long-term effect on boxing-specific performance outcomes remains underexplored.MethodsTwenty-eight male collegiate boxers were randomly assigned to a VBT group (n = 14) or a PBT group (n = 14) for an 8-week training program. Both groups performed four sets of each exercise (back squat, Bulgarian split-squat, and deadlift) at 70% of their one-repetition maximum (1RM). The VBT group performed a flexible number of repetitions until their velocity dropped below a 10% threshold, whereas the PBT group consistently performed sets of 5 repetition. Pre- and post-intervention assessments included 1RM strength, countermovement jump (CMJ) height, standing long jump (SLJ) distance, and 30 m sprint run time.ResultsAll dependent variables demonstrated significant main effects of “time” (p < 0.001; averaged Hedges’ g = 0.44 for VBT group and 0.23 for PBT group). Notably, significant “time” × “group” interactions were observed for the CMJ, SLJ, and 30 m sprint run (p ≤ 0.038), whereas no significant interactions were found for 1RM strength measures across exercises (p ≥ 0.163). Furthermore, when comparing the magnitude of changes between groups, the VBT group exhibited small effect size improvements in CMJ height (Hedges’ g = 0.41), SLJ distance (Hedges’ g = 0.56), and 30 m sprint time (Hedges’ g = 0.51). In contrast, all other variables only showed trivial (Hedges’ g < 0.20) differences between groups.ConclusionBoth training programs led to comparable improvements in maximal strength (1RM) across exercises. However, VBT was more effective than PBT in enhancing performance in high-velocity tasks such as vertical and horizontal jumps and sprinting. These findings support the use of VBT to optimize neuromuscular adaptations relevant to explosive actions in male collegiate boxers.